Node Cooperation to Avoid Early Congestion Detection Based on Cross-Layer for Wireless Ad Hoc Networks - Abdalrazak Tareq Rahem; Mahamod Ismail; Nor Fadzilah Abdullah; Mohammed Balfaqih (Institute of Advanced Engineering and Science, 2016)
The resent application of wireless ad hoc networks (WANET) demands a high and reliable data load. The simultaneous transfer of large amounts of data different nearby sources to nearby destinations in a massive network under these circumstances results in the possibility of network congestion. Congestion is an extremely unwanted condition because it creates extra overhead to the already deeply loaded environment, which ultimately leads to resource exhaustion, and can lead to packet drops and retransmission at either the MAC or upper layers. We present a lightweight congestion control and early avoidance congestion control scheme, which can effective control congestion while keeping overhead to a minimum. This scheme is based on the Cross-layer between the MAC and network layers lead to early detection of congestion. With the help of node cooperation the sender node is triggered to find an alternative route based on TMT. This mechanism controls the network resources rather than the data traffic. Detailed performance results show enhancement in the throughput and packet delivery ratio, as well as a reduction in packet drop. Generally, network performance increases.